2018
DOI: 10.1167/iovs.17-22931
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Linked Kinase Controls Choroidal Neovascularization by Recruitment of Endothelial Progenitor Cells

Abstract: We demonstrate that ILK controls the development of CNV by regulating the recruitment of EPC to CNV lesions, possibly through ILK-dependent expression of SDF-1 and VEGF in RPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Disturbances in the balance of secretory proangiogenesis and antiangiogenesis factors trigger an angiogenic switch that fuels DR progression. In the present study, CM from the hypoxia group increased the microvascular density in the Matrigel plug, which is consistent with previous conclusions (Zhu et al, 2016 (Yang, Duan, Zhang, Qu, & Wang, 2018;Yang et al, 2009). In addition, HIF-1α has been demonstrated to bind to hypoxia response elements within the Sp1 promoter to stimulate Sp1 gene transcription activity (Higashimura et al, 2011;Woo et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Disturbances in the balance of secretory proangiogenesis and antiangiogenesis factors trigger an angiogenic switch that fuels DR progression. In the present study, CM from the hypoxia group increased the microvascular density in the Matrigel plug, which is consistent with previous conclusions (Zhu et al, 2016 (Yang, Duan, Zhang, Qu, & Wang, 2018;Yang et al, 2009). In addition, HIF-1α has been demonstrated to bind to hypoxia response elements within the Sp1 promoter to stimulate Sp1 gene transcription activity (Higashimura et al, 2011;Woo et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…One possible explanation for this may be that HIF-1α mediates this regulatory relationship. HIF-1α was originally identified as an oxygen-responsive activator and is upregulated in various cell lines, including ARPE-19 cells, under hypoxia (Yang, Duan, Zhang, Qu, & Wang, 2018;Yang et al, 2009). In addition, HIF-1α has been demonstrated to bind to hypoxia response elements within the Sp1 promoter to stimulate Sp1 gene transcription activity (Higashimura et al, 2011;Woo et al, 2012).…”
Section: Ing4 Regulates the Expression Of Several Proangiogenic Facto...mentioning
confidence: 99%
“…The beneficial effects of these factors on IVM have been demonstrated in several species, such as human [37,38], cow [39], horse [40], pig [41], and mouse [38]. In the present study, it was demonstrated that EPC can secrete various paracrine factors, including bFGF, VEGF, IGF-1, and IL-10, into the extracellular environment, which is consistent with previous findings [42][43][44]. Subsequently, the factors derived from EPC-CM effectively activate the mRNA transcript levels of the receptors (FGFR2 and IGF1R) on COCs during IVM.…”
Section: Discussionsupporting
confidence: 92%
“…Integrinlinked kinase (ILK) plays multifaceted roles in cellular functions such as cell migration, differentiation, survival, and division and importantly has been highlighted as a key regulator of longevity and of cellular senescence induced by extracellular stressors (Olmos et al, 2017). ILK is also found to be involved in choroidal neovascularization via recruitment of endothelial progenitor cells (Yang et al, 2018), which may be of interest as horseshoe crab is utilised for studies on visual physiology (Hartline et al, 1956;Barlow, 1983;Watson et al, 2008;Battelle, 2016;Battelle et al, 2016).…”
Section: Limulusmentioning
confidence: 99%